Gilbert syndrome and ischemic heart disease: a protective effect of elevated bilirubin levels - Vítek, Libor; Jirsa, Milan; Brodanová, Marie; Kalab, Milan; Marecek, Zdenek; Danzig, Vilém; Novotný, Ladislav; Kotal, Petr (Atherosclerosis, 2002)
BACKGROUND: Oxidation processes play an important role in atherogenesis. Bilirubin IXalpha is recognised as a potent antioxidant. In the present study, we assessed the role of elevated serum bilirubin levels in the prevention of ischemic heart disease (IHD). METHODS: The occurrence of IHD was determined in Gilbert syndrome (GS) patients above 40 years (n=50). The diagnosis was based on past medical history and ECG criteria. The occurrence was related to that of the comparable general population (n=2296). Serum biochemistry, including the total antioxidant status was evaluated in the GS subjects, IHD patients (n=38) and control subjects (n=38). RESULTS: The prevalence of IHD in GS subjects (aged 49.7+/-9.0 years) was 2% (0.05-10.7%, 95% confidence interval), compared to 12.1% in a general population (P<0.05). Bilirubin, total antioxidant capacity and high density lipoprotein (HDL) cholesterol were found to be significantly higher in GS subjects compared to control groups (P<0.05). According to linear discriminant analysis, hyperbilirubinemia rather than elevation of HDL cholesterol levels seemed to be more important in protection from IHD. CONCLUSIONS: In the present study, low prevalence of IHD in GS subjects was detected. It may be presumed that chronic hyperbilirubinemia prevent the development of IHD by increasing the serum antioxidant capacity.
Keywords: antioxidancia; Gilbertova nemoc; Male; HDL-cholesterol; Cholesterol, HDL; Adult; Bilirubin; bilirubin; dospělí; mužské pohlaví; Myocardial Ischemia; lidé; ženské pohlaví; Antioxidants; Humans; Gilbert Disease; ischemická choroba srdeční; Female; lidé středního věku; Middle Aged